Perubahan Bunyi Zeroisasi Dalam Pelafalan Lagu Penyanyi Lyodra - Putri, Sekar Hidayah; Siagian, Irwan (Peneliti.net, 2023)
Phonemic is part of the science of language, namely phonology. The type of study in this branch of phonology is phonemes. In everyday life, phonemes often have sound changes because in the use of speech, phonemes or language sounds are interrelated in a series of sounds. One of the causes of this sound change is due to historical developments. This change occurs due to adjustments to the agreement by language users in the local community and cultural environment. With this phoneme study, students' abilities will improve in terms of researching and also identifying one part of the type of phonemic study, namely phonemes. The use of methods in this study, namely by using qualitative methods or methods that focus on descriptive analysis. This research is divided into two data, namely the first data or the main data in the form of songs performed by singer Lyodra and the second data in the form of others such as books, journals, or articles. From the analysis of a song entitled